2022
DOI: 10.1186/s12935-022-02572-4
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-1-antichymotrypsin as a novel biomarker for diagnosis, prognosis, and therapy prediction in human diseases

Abstract: The glycoprotein alpha-1-antichymotrypsin (AACT), a serine protease inhibitor, is mainly synthesized in the liver and then secreted into the blood and is involved in the acute phase response, inflammation, and proteolysis. The dysregulation of AACT and its glycosylation levels are associated with tumor progression and recurrence, and could be used as a biomarker for tumor monitoring. In this review, we summarized the expression level, glycosylation modification, and biological characteristics of AACT during in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…The glycoprotein AACT is a serine protease inhibitor involved in the acute phase response and proteolysis (UniProtKB). Its dysregulation and glycosylation levels are associated with tumor progression and recurrence [ 40 ]. A1BG, another glycoprotein belonging to the immunoglobulin superfamily, was found overexpressed by proteomics in various forms of cancer, such as pancreatic ductal adenocarcinoma [ 41 ], cervical intraepithelial neoplasia [ 42 ] and bladder cancer [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The glycoprotein AACT is a serine protease inhibitor involved in the acute phase response and proteolysis (UniProtKB). Its dysregulation and glycosylation levels are associated with tumor progression and recurrence [ 40 ]. A1BG, another glycoprotein belonging to the immunoglobulin superfamily, was found overexpressed by proteomics in various forms of cancer, such as pancreatic ductal adenocarcinoma [ 41 ], cervical intraepithelial neoplasia [ 42 ] and bladder cancer [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, A1BG has been found to be associated with tumor heterogeneity and malignancy in an animal model of breast cancer [ 44 ]. Recently, its key role in tumorigenesis has been confirmed, suggesting that A1BG could be a promising target for cancer diagnosis, prognosis, and therapy [ 40 ]. Regarding A1AT, its high levels have been positively correlated with unfavorable clinical outcomes in cancer [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…A1AG2 (orosomucoid) was upregulated in idiopathic nephrotic syndrome and diabetic nephropathy and associated with disease progression [ 29 , 30 , 31 ]. AACT, a serine protease inhibitor, also termed SerpinA3, is mainly synthesized in the liver and protects against different inflammatory diseases [ 32 ]. Urinary AACT levels were positively correlated with preclinical renal fibrosis following AKI [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…But deficiency of ACT relates to liver disease, and in the case of BC, it is a prognostic favorable marker. Decreased ACT level was associated with poor survival in patients with liver cancer, increased ACT level was associated with shorter survival in patients with PDAC, and decreased ACT expression was associated with shorter survival in patients with early lung cancer [63]. Based on quantitative proteomics data it was suggested that the GlcNAcylated ACT will be a promising clinical biomarker in the diagnosis of early NSCLC [64].…”
Section: Alpha-1-antichymotrypsin (Aact_human)mentioning
confidence: 99%